2013
DOI: 10.3390/molecules18033458
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Pregnane Steroids from a South China Sea Gorgonian Carijoa sp.

Abstract: Abstract:A new pregnane steroid, 1, and three known analogues 2-4, have been isolated from a gorgonian Carijoa sp. collected from the South China Sea. The planar structure and relative configuration of 1 were elucidated from comprehensive spectroscopic data. Its absolute configuration was determined by application of the modified Mosher method. Compounds 1, 3 and 4 exhibited cytotoxicity against the human hepatoma cell line Bel-7402, with IC 50 values of 9.33, 11.02 and 18.68 µM, respectively. Additionally, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
0
14
0
3
Order By: Relevance
“…Pregnane 1021 (Carijoa sp., Weizou Is., S. China Sea) exhibited potent antimicrobial properties. 823 In addition to a number of known congeners, three new mildly cytotoxic polyhydroxylated steroids 1022-1024 were isolated from Sarcophyton sp. (Weizhou Is., S. China Sea).…”
Section: Sesquiterpenes Capillosananementioning
confidence: 99%
“…Pregnane 1021 (Carijoa sp., Weizou Is., S. China Sea) exhibited potent antimicrobial properties. 823 In addition to a number of known congeners, three new mildly cytotoxic polyhydroxylated steroids 1022-1024 were isolated from Sarcophyton sp. (Weizhou Is., S. China Sea).…”
Section: Sesquiterpenes Capillosananementioning
confidence: 99%
“…Two 9,11-secosteroidal glycosides, sinularosides A and B, isolated from the South China Sea soft coral Sinularia humilis, exhibited potent antimicrobial activity (Sun et al 2012). In our previous reports, 86 steroidal compounds were obtained from marine invertebrates and their symbiotic fungi, which exhibited cytotoxic, antiviral and antibacterial activities (Cao et al 2014;Sun et al 2015;Zhao et al 2013).…”
Section: Steroidsmentioning
confidence: 97%
“…Similarly, essential oils distilled from leaves of the plant Ageratum fastiqiatum of Minas Gerais, Brazil, which contains about 14.6% of nonadecane were shown to have antibacterial activity against S. aureus, Streptococcus mutans, Streptococcus faecalis, E. coli and Salmonella typhosa (Del-Vechio-Vieira et al, 2009). Recently, Zhao et al (2013) showed that a pregnane isolated from the marine organism Carijoa sp. exibit promising antibacterial activity against Pseudomonas putida with minimum inhibitory concentration value about five-fold more potent than ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%